Multilevel analysis of factors that influence overweight in children: research in schools enrolled in northern Brazil School Health Program - Renata Andrade de Medeiros Moreira; Tiago Ricardo Moreira; Glauce Dias da Costa; Luiza Carla Vidigal Castro; Rosângela Minardi Mitre Cotta (BMC, 2020)
Abstract Background The study evaluates children in schools that participate in the School Health Program in the Northern region of Brazil with the objective of assessing whether their schools interfered in the development of overweight/obesity and how individual and school environment variables behave according to contextual analysis. Methods The analyses were carried out with 1036 children from 25 municipal public schools in Northern Brazil that participated in the School Health Program. We evaluated both individual characteristics and scholar environment through univariate and multivariate logistic regressions to identify which of these factors were related to overweight/obesity as well as the effect of varying such associations. Results The considered individuals had an median age of 8 years, being 54.9% female and 27.8% presenting overweight/obesity. In multivariate logistic regression, the overweight/obesity variance in schools was 0.386 (individual variables) and 0.102 (individual and school variables), explaining 23.7% of the variation, reduction of ICC and MOR. The Akaike Information Criterion between the models was reduced and the likelihood ratio indicated better adequacy of the latter model. The investigated children had a greater chance of developing overweight/obesity when they performed 2+ sedentary activities/day, depending on school location as well as whether or not candies were sold in the school surroundings. On the other hand, a lower chance of developing overweight/obesity was identified in children that ate 5+ meals/day and practiced dance at school. Conclusion We observed that the variables inherent to both individuals and schools favored the development of overweight/obesity in children. It is relevant that scholar curriculums incorporate healthy eating interventions and encourage body practices associated with policies that restrain the sale of ultra-processed food in schools as well as the development of intersectoral actions between education and health to control childhood obesity.